Comparison of Mean Serum Calcium Levels in Pregnancy with and without Pregnancy Induced Hypertension - Rakhshanda Bano, Shazia Tahseen, Fatima Imran Butt, Usman Masood Butt, Imran Masood Butt, Ayesha Imran Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare mean serum calcium levels in pregnancy, with and without pregnancy induced hypertension. Study design: A Cohort study was done. Place and duration of study: Department of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, Lahore Unit III, from 1st January 2021 to 30th June 2021. Methodology: Two hundred patients with gestational age between 28 to 40 weeks, were included in the present study, 100 patients in group A (hypertension) and 100 in group B (normotensive). Results: The mean age of patients in group-A and group-B was 28.87 ± 4.32 years and 27.49±4.80 years respectively. The mean gestational age in group-A was 35.86±1.86 weeks and in group B was 35.90±1.36 weeks. The mean serum calcium level was 7.26±0.80mg in group A and 8.94±0.53mg in group B which is statistically significant (p <0.001). Conclusion: It is concluded that serum calcium levels in women with pregnancy induced hypertension (PIH) are lower than in normal pregnant women. The calcium supplementation appears to reduce the risk of pregnancy induced hypertension. Therefore, calcium consumption in pregnancy should be encouraged, especially during the second and third trimester of pregnancy. Keywords: Hypocalcemia, pregnancy induced hypertension, Normotensive patients.